Basic illocutions in the native languages of Brazil - Hengeveld, Kess; Bechara, Eli Nazareth; Camacho, Roberto Gomes; Guerra, Alessandra Regina; Oliveira, Taísa Peres de; Penhavel, Eduardo; Pezatti, Erotilde Goreti; Santana, Liliane; Souza, Edson Rosa Francisco de; Teixeira, Maria Luiza de Sousa (ALFA: Revista de Linguística, 2009)
This paper shows that the distribution of basic illocutions (defined as grammatical structures that can be related to a default communicative intentions) within and across the indigenous languages of Brazil can be described systematically in terms of a set of implicational hierarchies by means of which the existence of certain basic illocutions can be predicted from the existence of others. In doing so, a case is made for a major distinction between propositional and behavioural basic illocutions, the former having to do with the exchange of information, the latter with influencing behaviour.